The goodbye bride ebook - Hunter, Denise (Summer Harbor, 2016)
Zac knows that if he follows his heart he'll win back the love of his life—but if Lucy's memory returns, his would-be bride might say goodbye forever. Now a Hallmark Original movie! She only remembers loving him. But he can't forget the way she left. Lucy Lovett can't remember the last seven months of her life. She doesn't remember leaving her fiancé Zac Callahan weeks before their wedding or moving to Portland, Maine. And she sure doesn't remember getting engaged to another man. All she remembers is loving Zac more than life itself. Zac was just beginning to get his life back on track after Lucy left him with no explanation. And now she's back—vulnerable, homeless, and still in love with him. Has he been given a second chance with the only woman who stirs his passion and haunts his dreams? Lucy knows she must unlock those missing months and discover why she threw everything away. "I've been a longtime fan of Denise Hunter's, and The Goodbye Bride has everything I've come to love about her romances: a plucky heroine with lots of backstory, a yummy hero, and a terrific setting. Highly recommended!" —Colleen Coble USA TODAY bestselling author of the Lavender Tides and Hope Beach series "Can romance be any more complicated than a bride who doesn't remember running away from her groom? Denise Hunter's take on a woman's attempt to find her way back to happily ever after again is sweetly endearing. Readers will keep turning pages, wanting to know how true love ever went so wrong . . . and if The Goodbye Bride gets her chance to say "I do." —Beth K. Vogt, 2015 RITA® Finalist and author of Crazy Little Thing Called Love "Denise Hunter has done it once again, placing herself solidly on my must-read list! The Goodbye Bride is a tender, thoughtful look at the role memories play in a romance. The clever plot kept me up way past my bedtime—and happy to be so!" —Deborah Raney, award-winning author of the Chicory Inn Novels series "The Goodbye Bride highlights the abandonment that so many have experienced. More importantly, within the context of a wonderful Summer Harbor romance, the author deftly illustrates that there is One who will never abandon us, and when we trust Him, we can in turn trust the people He places in our lives. All this packaged inside one heart-stopping, page-turning romance that will leave the pickiest romance reader delighted and asking for just a few more pages." —Cara C. Putman, award-winning author of Where Treetops Glisten and Shadowed by Grace Full-length Contemporary Romance Includes Discussion Questions for Book Clubs Now a Hallmark Original movie: An Unforgettable Christmas Part of the Summer Harbor series Book One: Falling Like Snowflakes Book Two: The Goodbye Bride Book Three: Just a Kiss